Penerapan Model Pembelajaran Inkuiri Untuk Meningkatkan Hasil Belajar Siswa SMA Negeri 1 Sirombu Tahun Pembelajaran 2024/2025 - Hidayanti Waruwu; Piderman Gulo (Program Studi Pendidikan Biologi - Universitas Nias, 2025)
The low biology learning outcomes of class X IPA 2 students of SMA Negeri 1 Sirombu, indicated by an average odd semester score of 56.80, is the main problem in this study. This condition is caused by the dominance of the lecture method in learning, which results in students being passive and less involved in the learning process. This study aims to describe the quality of the biology learning process and describe student learning outcomes through the application of the inquiry learning model. This classroom action research was conducted in two cycles with 36 class X IPA 2 students of SMA Negeri 1 Sirombu as research subjects. Each cycle consisted of three learning meetings and one evaluation. The instruments used included student and teacher activity observation sheets, learning quality questionnaires, interview guides, and learning outcome tests. The results showed that the quality of the learning process in cycle I reached 57.69% with a poor category, then increased significantly to 89.50% with a very good category in cycle II. The average student learning outcomes increased from 66.01 (sufficient category) in cycle I to 87.64 (very good category) in cycle II with learning completeness reaching 100%. These findings prove that the effective application of the inquiry learning model can improve the quality of students' biology learning processes and outcomes.